Multi-Functional Hypercrosslinked Polystyrene as High-Performance Adsorbents for Artificial Liver Blood Purification - Liu, Yunhong; Peng, Xinyan (Frontiers in Chemistry, 2022)
In artificial liver blood purification system, highly efficient removal of multiple toxic metabolites from whole blood by hemoperfusion still remains a challenge in the clinical field, due to the limited unspecific absorptive capacity and low biocompatibility of adsorbents. In this work, a new pyridinyl-modified hypercrosslinked polystyrene (HCP) adsorbent, named HCP(St-DVB-VP), was constructed directly through a Friedel-Crafts post-crosslinking reaction using a small-molecule crosslinking agent for the first time. The preparation method provides in this study can avert the problem posed by the use of the toxic carcinogenic chloromethyl ether reagent in the traditional HCP resin synthesis process. The results indicated that HCP(St-DVB-VP) had a highly porous structure with a specific surface area of 761 m2 g-1. Notably, the adsorbent demonstrated excellent adsorptive properties towards both protein-bound toxins (bilirubin) and medium- and large-sized molecular toxins (PTH, IL-6) in vitro experiments simultaneously. More importantly, the obtained adsorbent showed satisfactory hemocompatibility. Taken together, the low-cost and ecofriendly fabrication method, broad-spectrum adsorption performance and hemocompatibility makes the HCP(St-DVB-VP) promising for whole blood perfusion in artificial liver blood purification in clinical practice.